Реалізація та інтеграція однопараметричної моделі Раша в систему дистанційого навчання Moodle - Заміховський, Л. М.; Ходак, Л. М. (Eastern-European Journal of Enterprise Technologies, 2020)
This article presents causes of usage of Rasch model and process of buidling specific math engine and it’s integration into LMS Moodle